2014
DOI: 10.1002/hep.27340
|View full text |Cite
|
Sign up to set email alerts
|

Costs of telaprevir-based triple therapy for hepatitis C: $189,000 per sustained virological response

Abstract: Introduction In registration trials, triple therapy with telaprevir (TVR), pegylated-interferon (IFN), and ribavirin (RBV) achieved sustained virological response (SVR) rates between 64–75%, but the clinical effectiveness and economic burdens of this treatment in real-world practice remain to be determined. Methods Records of 147 patients who initiated TVR-based triple therapy at the Mount Sinai Medical Center (5/2011–12/2011) were reviewed. Direct medical costs for pre-treatment, on-treatment, and post-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
4
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 47 publications
(98 reference statements)
1
40
4
1
Order By: Relevance
“…In one study, out of a total of 147 patients who received TVR triple therapy, 44% obtained SVR with a median cost of $188,859 per SVR 24. The unexpected finding was that almost half the costs spent were on patients not obtaining SVR, as well as the cost associated with the management of adverse events and cost associated with the premature discontinuation of treatment [81]. In another study, Sethi et al found that the mean cost of treatment was $172,889 for treatment with a protease inhibitor.…”
Section: Cost Of Therapy In the Era Of Daasmentioning
confidence: 91%
See 1 more Smart Citation
“…In one study, out of a total of 147 patients who received TVR triple therapy, 44% obtained SVR with a median cost of $188,859 per SVR 24. The unexpected finding was that almost half the costs spent were on patients not obtaining SVR, as well as the cost associated with the management of adverse events and cost associated with the premature discontinuation of treatment [81]. In another study, Sethi et al found that the mean cost of treatment was $172,889 for treatment with a protease inhibitor.…”
Section: Cost Of Therapy In the Era Of Daasmentioning
confidence: 91%
“…In one study, costs of obtaining SVR with these regimens ranged from D 66,885 to D 120,350 depending on which triple therapy combination (boceprevir or telaprevir/PEGINF/RBV) was used. These costs were lower for patients who were compliant with treatment [81]. In another study using data from the French national hospital database, investigators determined that the discounted lifetime costs increased with the severity of fibrosis at diagnosis and that treatment with triple therapy increased discounted lifetime costs which were 20% (F2), 28% (F3) and 79% (F4) [79].…”
Section: Cost Of Therapy In the Era Of Daasmentioning
confidence: 95%
“…Furthermore, in the era of new DAAs, our findings may also provide evidence to obviate unnecessary protease inhibitor 39 or to conduct RGT based on HCV genotype and pretreatment/on-treatment viral kinetics when applying DAA plus Peg-IFN/RBV combination therapy for HBeAg-negative chronic dual HCV/HBV infections. 40 In conclusion, RGT with Peg-IFN plus RBV according to HCV genotype, baseline HCV VL and RVR had comparable efficacy as GGT for HBeAg-negative HBV/HCV dually infected patients. Strategy of RGT with abbreviated regimens may be considered for the clinical settings.…”
Section: Discussionmentioning
confidence: 77%
“…From 2015, interferonfree anti-HCV regimens with short treatment duration and fewer side effects will be available [84,85,103] . However, peginterferon may still have a role in resource-limited regions due to high cost of DAAs [104] . CHC patients achieved a SVR after anti-HCV treatments exhibited a reduction in all-cause mortality > 50% compared with those who are non-responders [82] .…”
Section: Treatmentmentioning
confidence: 99%
“…The cure rate for HCV infection is expected to be over 95% with the new all-oral, interferon-free regimens within the next few years. However, due to drug resistance [109,110] , suboptimal activity against certain HCV genotypes and the extremely high cost [100,104] , not all patients can be cured. Currently, no effective vaccine is available for HCV infection.…”
Section: Treatmentmentioning
confidence: 99%